2006
DOI: 10.1136/ijgc-00009577-200605000-00018
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of the level of awareness and utilization of the Pap smear as a cervical cancer screening test among female health workers in a tertiary health institution

Abstract: Papanicolaou (Pap) smear test is considered the best approach to reduce cervical cancer incidence worldwide. We surveyed 195 female health workers with structured questionnaires to identify factors that could influence the awareness and utilization of the Pap smear as a cervical cancer screening test. More than 65% of the respondents were aware of the disease, cervical cancer, and approximately 64% were aware of the Pap smear test. Seven three (39.7%) of the respondents had their sexual debut (coitarche) befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…More than 80% of the participants were aware of cervical cancer, including some of its modes of presentation and complications, and screening for cervical cancer. Thus, the awareness level documented is higher than the 37.5% awareness reported from Afikpo in the same Ebonyi State southeast Nigeria (Eze et al, 2012), 18.7% and 67% from Ibadan and Ogbomoso in southwest Nigeria (Kene, Saleh, & Nandul, 2006;Idowu et al, 2016) and 67.3% from Zaria, northwest Nigeria (Yahya & Mande, 2019), but similar to the findings of cervical cancer awareness of 79.8%, 64.0%, 80.0%, 72.9%, 94.0% in Nnewi in the southeast, Benin in the south-south, Lagos in the southwest, Jos in the north-central, and Maiduguri in the northeast respectively (Udigwe, 2006;Gharoro & Ikeanyi, 2006;Okunowo et al, 2018;Oyebode, Sagay, Ekwempu, & Daru, 2006;Bakari, Takai, & Bukar, 2015). This study shows that 32% of the participants who were aware of cervical cancer had undergone cervical cancer screening in the past.…”
Section: Discussionsupporting
confidence: 61%
“…More than 80% of the participants were aware of cervical cancer, including some of its modes of presentation and complications, and screening for cervical cancer. Thus, the awareness level documented is higher than the 37.5% awareness reported from Afikpo in the same Ebonyi State southeast Nigeria (Eze et al, 2012), 18.7% and 67% from Ibadan and Ogbomoso in southwest Nigeria (Kene, Saleh, & Nandul, 2006;Idowu et al, 2016) and 67.3% from Zaria, northwest Nigeria (Yahya & Mande, 2019), but similar to the findings of cervical cancer awareness of 79.8%, 64.0%, 80.0%, 72.9%, 94.0% in Nnewi in the southeast, Benin in the south-south, Lagos in the southwest, Jos in the north-central, and Maiduguri in the northeast respectively (Udigwe, 2006;Gharoro & Ikeanyi, 2006;Okunowo et al, 2018;Oyebode, Sagay, Ekwempu, & Daru, 2006;Bakari, Takai, & Bukar, 2015). This study shows that 32% of the participants who were aware of cervical cancer had undergone cervical cancer screening in the past.…”
Section: Discussionsupporting
confidence: 61%
“…Most of the female health workers in our study had been previously screened for cervical cancer. Other studies have documented a much lower uptake of cervical cancer screening by female health workers than in our study and those ranged from 6 to 41% [8,13,53,54,56,57,[61][62][63][66][67][68][69][70][71][72][73]. Female health workers who were not screened for cervical cancer cited various reasons for not attending screening including lack of access to screening services, misbeliefs about cervical cancer and screening, fear of the results and nonchalant attitude towards screening for cervical cancer.…”
Section: Discussionmentioning
confidence: 51%
“…Our finding agrees with earlier studies that reported low level of practice even when the good knowledge is good. 9 15 19 20 Studies by Aboyeji et al ., 11 , Gharoro et al ., 20 and Adefuye 14 reported other reasons to include ignorance, misconceptions and religious beliefs. These were similar to the reasons adduced in our study.…”
Section: Discussionmentioning
confidence: 99%